Ecotoxicological and potential endocrine effects of selected aquatic herbicides on life stages of the African clawed frog, Xenopus laevis - Babalola, Oluwaseun Olusegun (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.